IS THERE ANY SIGNIFICANT IMPACT OF TWO DIFFERENT BIO-COMPATIBLE COATED CARDIOPULMONARY BYPASS CIRCUITS ON CIRCULATING PLATELET DROP - SALEEM, M; KHAN, LN; MUSHTAQ, A (Biological and Clinical Sciences Research Journal, 2023)
Bleeding is common in cardiopulmonary bypass (CPB) surgery due to malfunctioning platelets. This study investigated the effect of a phosphorylcholine (PC)-coated CPB circuit and a balanced CPB circuit on platelet function. We conducted a descriptive, randomized trial at the Punjab Institute of Cardiology with 50 patients undergoing coronary artery bypass graft (CABG) surgery (n=34), valve surgery (n=10), and CABG plus valvular replacement (n=6) using CPB. The patients were divided into groups 1, which had phosphoryl-coated CPB, and 2, which had balanced-coated CPB. We measured and recorded pre- operative and post-operative levels of platelet count, white blood cells, and hemoglobin for both groups. We used the Student’s t- test to make comparisons among groups, and the P values for both groups were less than 0.05 at a 95% confidence interval, indicating a significant impact of biocompatible coated CPB circuits on circulating platelet drop. Cohen’s d formula showed that group 1 (Phosphoryl choline coating) had a more substantial effect on platelet drop than group 2 (Balanced coating). Blood component conservation, particularly platelet conservation, depends on the non-endothelium biocompatible surface used; the better the character, the more blood cells may be conserved. We looked at two coatings, phosphoryl coating, and balanced coating, to see if they substantially influenced platelet drop. According to the findings of our investigation, phosphoryl-coated CPB had a more significant influence on platelet drop than balanced coating.